2020
DOI: 10.1007/s42729-020-00232-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Wheat and Soybean Yields in a Subtropical Oxisol Through Effective P Fertilization Strategies

Abstract: Phosphorus (P) deficiency limits agricultural production in tropical and subtropical soils, where soil mineralogy is dominated by kaolinite, iron, and aluminum oxides. The aim of this work was to compare two application methods of P, to the soil surface and to the sowing line, to determine the most effective strategy to increase wheat and soybean yields on an oxidic subtropical soil in Brazil under field conditions. Additionally, four inorganic P fertilizers (monoammonium phosphate (MAP); single superphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Recently, in comparison with other P fertilizer sources, Fink et al, [22] found that significantly higher yields of wheat grains were obtained when plants were fertilized with natural rock P (NP; 14% P2O5) and monoammonium phosphate (MAP; 48% P2O5), followed by single superphosphate (SS; 18% P2O5) and those non fertilized with P, and, finally, wheat plants were fertilized with triple superphosphate (TP; 41% P2O5). They confirmed the superiority of natural rock phosphate over others.…”
Section: Grain Yieldmentioning
confidence: 99%
“…Recently, in comparison with other P fertilizer sources, Fink et al, [22] found that significantly higher yields of wheat grains were obtained when plants were fertilized with natural rock P (NP; 14% P2O5) and monoammonium phosphate (MAP; 48% P2O5), followed by single superphosphate (SS; 18% P2O5) and those non fertilized with P, and, finally, wheat plants were fertilized with triple superphosphate (TP; 41% P2O5). They confirmed the superiority of natural rock phosphate over others.…”
Section: Grain Yieldmentioning
confidence: 99%